ACQUISITION AND APPLICATION OF MUSIC LISTENING SKILLS FOR TEENAGERS - Zakovska, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Living in a society means there is a constant communication between its members. However, it is possible only when there is mutual understanding, because base principals of communication are the ability to communicate, emotional and physical readiness for communication, speaking and listening experience, as well as, mutual attitude between the talker and listener and vice versa. Listening to music is closely related to general ability to listen and perceive what has been heard. That is why the act of music listening under the guidance of a professional teacher is very important. Relevant requirement is the choice of qualitative learning content and diverse methods which are fit to teenager`s age that promote their intellectual and emotional growth. The results of the Research show that teenagers themselves believe to be very good listeners, but the answers to the test questions verify quite the opposite – teenagers are weak listeners. The aim of the research is to find out the possibilities of learning music listening skills for teenagers in school`s pedagogical process and its practical use in everyday life. The methods used: analysis of scientific literature, pedagogical observation, testing, questionnaire.